Pertanggungjawaban Terhadap Tindak Pidana Penyelundupan Sepeda Motor Harley oleh Direktur PT. Garuda Indonesia - I Dewa Gede Pramana Adhi; I Nyoman Gede Sugiartha; Made Minggu Widiantara (Fakultas Hukum Universitas Warmadewa, 2021)
Indonesia is a developing country where each region has its own natural wealth. This advantage cannot be utilized because of the number of people who send out of the area without permission and vice versa goods from outside countries smuggled into Indonesi a only to avoid the applicable taxes. 1) What is the regulation of smuggling crimes in indonesian criminal law? 2) What is the accountability of the director of PT. Garuda Indonesia who carried out the act of smuggling luxury motorcycles? This research is a type of normative law research conducted by a research method of reviewing based on legal materials, while the problem approach used is the approach of legislation - legislation and conceptual. A bad example was again shown by one of the people who have a big name in Indonesia smuggling case by garuda Indonesia dirut become a picture of how weak the law in Indonesia and this incident makes the perpetrator can be criminal and administrative sanctions.